Individual electronic defect states in a-Si:H/a-SiNx double barrier structures - Hundhausen, Martin; Ley, Lothar; et al. (Journal of Non-Crystalline Solids, 1991)
Random telegraphic noise (RTN) in large area a-Si:H/a-SiNx:H double barrier structures (DBS) is due to the charging and discharging of individual trap states in the barrier layer. The effective device area is confined to a path of less than 10 μm diameter. This is verified through the local effect a focused laser beam has on the noise characteristics. The capture (τ-c) and emission (τ-e) time constants of the current controlling trap can be determined separately. Temperature and bias dependence of the time constants are discussed within a model of acceptor-like traps with strong electron-lattice coupling that are situated in the nitride barrier and exchange charge with the conduction electrons in the adjacent n+a-Si:H layers. © 1991 Elsevier Science Publishers B.V. All rights reserved.
UnivIS-Import:2015-03-05:Pub.1991.nat.dphy.IAP.exphys.indivi